The Relationship Between Humor Styles and Forgiveness - William Hampes (Europe's Journal of Psychology, 2016)
Research has shown that a factor in a victim’s forgiveness of an offender is the victim’s ability to make more positive, or at least less negative, attributions of the offender’s behavior and that perspective-taking can be a factor in facilitating that process. Self-enhancing humor has been found to be positively correlated with perspective-taking empathy and aggressive humor found to be negatively correlated with perspective-taking empathy. Therefore it was predicted that self-enhancing humor would be positively correlated with forgiveness and aggressive humor negatively correlated with forgiveness. The Humor Styles Questionnaire, the Absence of Negative and Presence of Positive subscales of the Forgiveness Scale, and the Forgiveness Likelihood Scale were administered to 112 college undergraduates. Self-enhancing humor was significantly and positively correlated with all of the forgiveness measures, aggressive humor and self-defeating humor were significantly and negatively correlated with some of the forgiveness measures and affiliative humor was not significantly correlated with any of the forgiveness measures. The results were interpreted in terms of previous findings for humor styles, perspective-taking empathy, depression, self-esteem and anxiety. Future research involving the extent to which other personality variables, such as perspective-taking empathy, mediate the relationship between self-enhancing humor and forgiveness was suggested.